2006
DOI: 10.1111/j.1574-6941.2005.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of mycorrhization helper bacteria cell density and metabolite localization for the Pinus sylvestris–Lactarius rufus symbiosis

Abstract: Mycorrhization helper bacteria, Paenibacillus sp. EJP73 and Burkholderia sp. EJP67, were used to study the importance of bacterial inoculum dose and bacterial derived soluble and volatile metabolites localization for enhancing mycorrhiza formation in the Pinus sylvestris-Lactarius rufus symbiosis, using a laboratory based microcosm. EJP73 and EJP67 produced different responses in relation to the inoculum dose; EJP73 significantly enhanced mycorrhiza formation to the same degree at all doses tested (10(5), 10(7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 26 publications
(49 reference statements)
1
20
0
Order By: Relevance
“…flavonoids (AMF) and furans (ECM), that facilitate the growth of fungal hyphae and the subsequent colonization of plant roots by ECM (Founoune et al 2002;Duponnois and Plenchette 2003;Aspray et al 2006;Riedlinger et al 2006) and AM fungi (Duponnois and Plenchette 2003;Hildebrandt et al 2002Hildebrandt et al , 2006. Hildebrandt et al (2002Hildebrandt et al ( , 2006 have demonstrated that certain compounds (including raffinose and other unidentified metabolites) produced by strains of Paenibacillus can directly enhance the growth of AMF extraradical mycelium.…”
Section: Mechanism 1: Biochar Changes Soil Nutrient Availabilitymentioning
confidence: 99%
“…flavonoids (AMF) and furans (ECM), that facilitate the growth of fungal hyphae and the subsequent colonization of plant roots by ECM (Founoune et al 2002;Duponnois and Plenchette 2003;Aspray et al 2006;Riedlinger et al 2006) and AM fungi (Duponnois and Plenchette 2003;Hildebrandt et al 2002Hildebrandt et al , 2006. Hildebrandt et al (2002Hildebrandt et al ( , 2006 have demonstrated that certain compounds (including raffinose and other unidentified metabolites) produced by strains of Paenibacillus can directly enhance the growth of AMF extraradical mycelium.…”
Section: Mechanism 1: Biochar Changes Soil Nutrient Availabilitymentioning
confidence: 99%
“…The membership of the Burkholderia genus to MHB is reported by several authors [20,1,2,16]. In particular, attention deserves Poole et al (2001), who isolated this type of bacteria from symbiotic connection of Pinus sylvestris -Lactarius rufus.…”
Section: Characteristics Of Species Compositionmentioning
confidence: 87%
“…A similar situation occurs in the layer of soil directly associated with mycorrhizal roots for which Linderman (1988) [19] suggested the name "mycorrhizosphere". Organisms inhabiting enriched rhizosphere are plant pathogens, opportunistic commensals, saprophytes, and associated with roots "co-workers" as well as endosymbiotes [19,1].…”
Section: Introductionmentioning
confidence: 99%
“…Ravnskov et al (2002) observed similar differential effects of five strains of the biocontrol bacterium Burkholderia cepacia on the growth of the external mycelium of G. intraradices. Aspray et al (2006b) proposed that the expression of activities of helper bacteria depend on a variety of interacting factors, including cell density. In the present experiment the different Paenibacillus isolates were not quantified, but a food base was added in terms of TSB why the bacteria most likely were actively growing at least for a period during the experiment.…”
Section: Discussionmentioning
confidence: 99%